Effect of Stocking Density on the Growth Performance of Sex Reversed Male Nile Tilapia (Oreochromis niloticus) Under Pond Conditions in Tanzania - Kapinga, Imani; Mlaponi, Enock; Kasozi, Nasser (World, 2014)
A study was conducted to compare the growth potential of monosex Nile tilapia at two different stocking densities. Fish of 2.6±0.1g average weight were stocked in ponds at the stocking density of 3fish/m2 (low stocking density ‘LD’) and 13fish/m2 (high stocking density ‘HD’) respectively. Locally feed (CP; 25 %) was administered at 5% of body weight three times a day for five months. Monthly sampling was conducted to assess growth by measuring weight and length of 30 fish from both systems to obtain the average weight and length for specific growth rate (SGR), feed conversion ratio (FCR), average daily gain (ADG), weight gain (WG) and Biomass (BM). There was significantly higher (p<0.05) fish growth performance in LD ponds; SGR (3.47%), ADG (0.57g), WG (83.5g) compared to HD; SGR (2.71%), ADG (0.27g) and WG (40.8g). BM in HD was significantly higher (565.3g) compared to LD (258.3). There was no significant difference (p>0.05) in FCR, although lower value was in HD (2.46) than LD (2.71). The differences in performance of Tilapia in the two stocking densities could have been attributed to stress, competition for food and living space. However, HD gave significantly higher biomass yield per area than LD and can be very useful to give good returns for local consumption and where resources like land, water and capital are inadequate. There is therefore need to determine the optimum management levels necessary to boost fish growth of under high-density systems.
Keywords: Feed Conversion Ratio; Nile Tilapia; Specific Growth Rate; Biomass